Engaged environmental science for underserved youth. Issue 9 (2nd September 2019) - Kirsch, Katie R.; Elizondo, Juan; De Hoyos Salazar, David; Washington, Steven; Burdick, Travis; Alvarez, Pablo; Horney, Jennifer A.
Abstract: The National Institute for Environmental Health Sciences has called for targeted efforts to engage underserved youth in environmental education programs that support environmental literacy and contribute to the development of a diverse workforce pipeline for environmental science-related occupations. Evidence suggests that career knowledge among low income and minority youth is more likely to be incompatible with post-secondary educational opportunities than other racial and ethnic groups. One approach to attenuating discordant college and career expectations among underserved youth is building networks for information sharing between secondary and post-secondary students. The purpose of this commentary is to describe the development and implementation of a high school curriculum on environmental science and environmental justice by Texas A&M University in collaboration with community engagement partners, students, and teachers at Furr High School, an innovative XQ Super School in Houston, Texas.